2014
DOI: 10.1891/0198-8794.34.189
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Individual Differences in Human Health and Longevity

Abstract: In this chapter, we review of the fi eld of gerontological genetics with respect to subjective and objective health, the role of stress on health, and fi nally frailty and longevity. For most indices of subjective and objective health, frailty, and longevity, genetic infl uences contribute only modestly to individual differences, wherein heritabilities are typically on the order of 35%-40%. Notable exceptions are the moderate to strong heritabilities for lipid measures and brain structure and function, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 158 publications
(190 reference statements)
0
7
0
Order By: Relevance
“…Sex differences were also evident in the extent of genetic variance across question types, with generally more genetic variance in SH for women than for men. These results suggest that men may rely more on cultural conceptions of health when evaluating their own health, whereas women may rely more on physical health conditions, which reflect greater genetic influences than SH measures (Finkel et al, 2014). One reason for this sex difference in conceptualizations of SH may be the differential experience of physical aging between men and women.…”
Section: Longitudinal Changes In Subjective Health Variancementioning
confidence: 87%
See 3 more Smart Citations
“…Sex differences were also evident in the extent of genetic variance across question types, with generally more genetic variance in SH for women than for men. These results suggest that men may rely more on cultural conceptions of health when evaluating their own health, whereas women may rely more on physical health conditions, which reflect greater genetic influences than SH measures (Finkel et al, 2014). One reason for this sex difference in conceptualizations of SH may be the differential experience of physical aging between men and women.…”
Section: Longitudinal Changes In Subjective Health Variancementioning
confidence: 87%
“…Twins in these samples shared their rearing socioeconomic status and may have learned healthy lifestyles in their childhood years that continue to influence their behavior in late adulthood (eg, (Seeman & Crimmins, 2001). Most twin research indicates, however, that the impact of rearing environment tends to decrease with increasing age for many traits, including physical health and other relevant components of SH (eg, (Finkel et al., 2014;Reynolds et al, 2005). Additionally, evidence suggests that SH is influenced primarily by recent events or current SES levels, as opposed to distal factors (Manderbacka & Lundberg, 1996;Verropoulou, 2012).…”
Section: Longitudinal Changes In Subjective Health Variancementioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for the heritability of SRH comes from several twin studies, [15][16][17] which provide estimates of the percentage variance explained by genetic factors which range from ~20% to ~60%. 18,19 Studies using molecular genetic methods also provide evidence for heritability: for instance, the genome-wide complex trait analysis (GCTA-GREML) method 20 was used to estimate that common SNPs account for 18% of the variation in SRH (N = 4233). 21 A multivariate twin study 22 indicated appreciable genetic overlap between SRH and the phenotypically-correlated traits of optimism and self-rated mental health.…”
Section: Introductionmentioning
confidence: 99%